Heterocyclic and Alkyne Terpenoids by Terpene Synthase‐Mediated Biotransformation of Non‐Natural Prenyl Diphosphates: Access to New Fragrances and Probes. (29th September 2022) - Weigel, Benjamin; Ludwig, Jeanette; Weber, Roman A.; Ludwig, Steve; Lennicke, Claudia; Schrank, Paul; Davari, Mehdi D.; Nagia, Mohamed; Wessjohann, Ludger A.
Abstract: Two terpene cyclases were used as biocatalytic tool, namely, limonene synthase from Cannabis sativa (CLS) and 5‐ epi ‐aristolochene synthase (TEAS) from Nicotiana tabacum . They showed significant substrate flexibility towards non‐natural prenyl diphosphates to form novel terpenoids, including core oxa‐ and thia‐heterocycles and alkyne‐modified terpenoids. We elucidated the structures of five novel monoterpene‐analogues and a known sesquiterpene‐analogue. These results reflected the terpene synthases′ ability and promiscuity to broaden the pool of terpenoids with structurally complex analogues. Docking studies highlight an on‐off conversion of the unnatural substrates. Abstract : Terpene synthase‐mediated biotransformation of eleven synthetic sulfur‐ or oxygen‐containing non‐natural prenyl diphosphates resulted in the formation of five novel terpenoids and analogues. Uniquely, they trap intermediate steps and form heterocycles or compounds with alkyne side chains. Computational modelling differentiates convertible from inconvertible substrates and thereby provides an understanding of the detailed molecular mechanism of terpene cyclases.